Evaluation of a "walk-through" ladder top design during ladder-roof transitioning tasks. (March 2017) - Simeonov, P.; Hsiao, H.; Powers, J.; Ammons, D.; Kau, T.; Cantis, D.; Zwiener, J.; Weaver, D.
Abstract: This study evaluated the effect of an extension ladder "walk-through" top design on kinetic and kinematic behaviors and the outward destabilizing forces induced on the ladder during transitioning at elevation. Thirty-two male participants performed stepping tasks between a ladder top and a roof at simulated elevation in a surround-screen virtual-reality system. The experimental conditions included a "walk-through" and a standard ladder top section supported on flat and sloped roof surfaces. Three force platforms were placed under the ladder section and in the roof to measure propulsion forces during transitions. A motion measurement system was used to record trunk kinematics. The frictional demand at the virtual ladder base was also calculated. The results indicate that under optimal ladder setup (angle 75.5 °), the frictional demand at the ladder base remains relatively small for all experimental conditions. Also, the "walk through" ladder top eased the ladder-to-roof transitions but not the roof-to-ladder transitions. Highlights: Differences in frictional demand between walk-through and regular ladder are small. Walk-through ladder design affords easier more confident movements for transition up. Transitioning down with walk-through and regular ladders remains challenging.